Epigenetic Regulation of Gill Function in Japanese Flounder Under Hypoxic Stress Analyzed via Genome-Wide Methylome and Transcriptome Dynamics - Hengtai Tang; Chengnan Ding; Tianyang Cai; Guangling Li; Pingping Liu; Zhirui Zhang; Feng He (Journal of Ocean University of China, 2026)

A prompt-guided differentiable physics model for flood forecasting in data-scarce basins - Jiru Zhang; Jun Feng; Runliang Xia; Pingping Shao; Xin Chi (Journal of Hydrology, 2026)

Vegetation in Central Asia is more sensitive to soil moisture stress than to precipitation and vapor pressure deficit stresses - Hongwu Liang; Guli Jiapaer; Cun Chang; Tao Yu; Liancheng Zhang; Pingping Feng; Kaixiong Lin; Tongwei Ju; Xiapeng Jiang; Philippe De Maeyer; Tim Van de Voorde (Agricultural and Forest Meteorology, 2026)

From lunar terrain to learned representations: A comparative study of crater extraction - Ersa Wei; Xiangmei Liu; Minxuan Gao; Feng Zhang; Pingping Lu; Yanan Dang; Jiahan Wang; Tao Wu; Jiaqi Chen (Icarus, 2026)

Vertical Distribution and Controls on Heavy Metal(loid)s in Shallow Fissure Soils of Karst Geochemical Background Regions - Liang Tai; Yong Niu; Jia Chen; Gang Li; Pingping Fan; Feng Zhang; Tingjun Tan; Kaiqian Shi (Water, Air, & Soil Pollution, 2026)

A data-driven and expert flood knowledge model based on the development of the Huber loss function for flood forecasting - Haider Malik; Jun Feng; Pingping Shao; Zaid Ameen Abduljabbar (Water Research, 2026)

Uncovering ecological risks of pesticides: From parent compounds to unknown transformation products in soils from Dongting Lake Basin - Lu Liu; Pingping Wang; Feng Li; Xiaoxiao Li; Meng Gao; Yiming Yao; Yu Wang; Zhipeng Cheng; Fei Ge; Hongwen Sun (Journal of Hazardous Materials, 2026)

VSIG4 Inhibits Microglia-Mediated Neuroinflammation and Neuronal Injury by Modulating the JAK2-STAT3/NF-κB Signaling Pathway in Parkinson’s Disease - Jingcong Zhuang; Pingping Cai; Zhongjie Chen; Quanlong Hong; Rong Wang; Feng Wang; Yaxin Zhang; Danjie Wu; Fengzhu Chen (Molecular Neurobiology, 2026)

BRCA-CN: a blockchain-based framework to support public variant databases sharing in multi-center community for diagnostic reference and China regulatory science - Shoufang Qu; Rongzhi Liu; Shisen Li; Chuanfeng Huang; Yingqian Zhang; Xuan Gao; Pingping Dai; Chao Xu; Rutao Yang; Xuchao Li; Guojun Ouyang; Kang Shao; et al. (Human Genetics, 2025)

Salcastaniols A-G, seven undescribed diterpenoids with cholinesterase inhibitory activities from Salvia castanea Diels f. tomentosa Stib - Zhaoyue Dong; Pingping Wang; Qingju Liu; Feng Ju; Miaomiao Sun; Mohammad Mahmoud Nagdy; Fancheng Meng; Guowei Wang; Zhihua Liao; Min Chen (Phytochemistry, 2025)

Hesperidin alleviates endothelial cell inflammation and apoptosis of Kawasaki disease through inhibiting the TLR4/IĸBα/NF-ĸB pathway - Yuting Guan; Jinghua Ruan; Pingping Tan; Songwei Qian; Size Zhou; Ao Zhang; Yuchong Fu; Shuhui Zhao; Yuqing Ran; Xing Feng; Yijia Wang; Xinlei Wu; et al. (Chemico-Biological Interactions, 2025)

Inversion of biophysical parameters of potato based on an active learning pool-based sampling strategy - Yuanyuan Ma; Xiaoyu Song; Jie Zhang; Di Pan; Haikuan Feng; Guijun Yang; Chunxia Qiu; Heguang Sun; Chunkai Zheng; Pingping Li (International Journal of Remote Sensing, 2025)

Morphological, physiological and transcriptional analyses provide new insights into the abnormal phenotype of the macroalga Agarophyton vermiculophyllum (Rhodophyta) - Pingping Li; Jiaxing Wang; Xiaoqing Feng; Jingyu Zhang; Yingtang Dong; Zheng Li; Feng Qin; Yiyi Hu; Zhenghong Sui (Aquaculture, 2025)

Spectral Analysis of Dissolved Organic Carbon in Seawater by Combined Absorption and Fluorescence Technology - Xuan Cao; Feng Xiong; Yang Wang; Haikuan Ma; Yanmin Zhang; Yan Liu; Xiangfeng Kong; Jingru Wang; Qian Shi; Pingping Fan; Yunzhou Li; Ning Wu (Journal of Marine Science and Engineering, 2024)
Dissolved organic carbon refers to soluble carbon substances in water bodies and can be used as an important indicator for water pollution. Spectroscopic detection is commonly used to detect dissolved organic carbon in seawater. However, independent spectral methods are susceptible to interference, and insufficient extraction of the data features can occur. Accordingly, this study introduces a multisource spectral fusion method that relies on a combination of principal component analysis and convolutional neural networks to construct the detection model. The Bayesian correction method is used for calibration, and the dissolved organic carbon content of 10 groups of unfiltered seawater samples is analyzed. Correcting the spectral data acquired from samples containing impurities significantly improved the linear correlation coefficient R2 of dissolved organic carbon from 0.8891 to 0.9838. Similarly, the mean absolute error was significantly reduced from 15.33% to 3.24%, while the individual absolute error was effectively controlled, remaining within 9%. The obtained results show that the developed method effectively integrates the ultraviolet absorption and fluorescence spectral data and overcomes interference from other substances using the Bayesian correction method. Overall, this provides a highly accurate detection system with potential applications in monitoring the marine environment.

Real-time predictive control assessment of low-water head hydropower station considering power generation and flood discharge - Yubin Zhang; Xiaoqun Wang; Tianyu Feng; Jijian Lian; Pingping Luo; Madhab Rijal; Wentao Wei (Journal of Hydrology, 2024)

Distribution mechanisms of soil surface erosion and underground leakage in karst areas of China: A systematic, quantitative review - Jia Chen; Pingping Fan; Feng Zhang; Tingjun Tan; Nufang Fang; Zeyan Wu; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Comparisons of stripe rust response, grain yield and quality between fungicide sprayed and non-sprayed treatments for newly developed wheat lines carrying different genes for adult-plant resistance to stripe rust - Hao Chen; Liangqi Zhang; Chuanguang Ding; Yuqi Luo; Guoyun Jia; Junming Feng; Yuqi Wang; Binfan Si; Jianian Zhou; Xin Li; Kebing Huang; Suizhuang Yang; et al. (Crop Protection, 2024)

The general patterns of water flow in loess slope system and implications for slope geological security - Li Feng; Maosheng Zhang; Hao Liu; Bin Zhang; Zhen Du; Pingping Sun; Junbo Bi; Liang Wang; Tianfeng Gu (Science of The Total Environment, 2024)

Resveratrol Ameliorates Retinal Ischemia-Reperfusion Injury by Modulating the NLRP3 Inflammasome and Keap1/Nrf2/HO-1 Signaling Pathway - Jiazhen Feng; Kaibao Ji; Yiji Pan; Pingping Huang; Tao He; Yiqiao Xing (Molecular Neurobiology, 2024)

One–third substitution of nitrogen with cow manure or biochar greatly reduced N2O emission and carbon footprint in saline–alkali soils - Sheng Zhang; Lihua Xue; Ji Liu; Pingping Jia; Ying Feng; Yi Xu; Zhijie Li; Xiaoning Zhao (Field Crops Research, 2024)

Development of a facile one-pot synthesized fluorescent green polyesters as cooling water antiscalants for industrial application - Lijun Gao; Tianming Gao; Jiuying Feng; Shaohong Mo; Yanbei Guo; Pingping Guo; Shiyun Pan; Yuqing Cheng; Qian Yang (Desalination, 2024)

Stability Analysis of Unsaturated Soil Pit Under Vehicle Load - Pingping Rao; Junjie Meng; Jifei Cui; Weikang Feng; Sanjay Nimbalkar; Zhiang Liu (Geotechnical and Geological Engineering, 2024)

Improving flood forecasting using time-distributed CNN-LSTM model: a time-distributed spatiotemporal method - Haider Malik; Jun Feng; Pingping Shao; Zaid Ameen Abduljabbar (Earth Science Informatics, 2024)

Atmospheric water demand dominates terrestrial ecosystem productivity in China - You Tu; Xiaofeng Wang; Jitao Zhou; Xiaoxue Wang; Zixu Jia; Jiahao Ma; Wenjie Yao; Xinrong Zhang; Zechong Sun; Pingping Luo; Xiaoming Feng; Bojie Fu (Agricultural and Forest Meteorology, 2024)

Fatty acids metabolism in ozone-induced pulmonary inflammatory injury: Evidence, mechanism and prevention - Mengyuan Li; Xiangbing Kong; Xiaotong Jian; Yacong Bo; Xinyi Miao; Huaiyong Chen; Pingping Shang; Xiaolei Zhou; Ling Wang; Qiao Zhang; Qihong Deng; Yuan Xue; et al. (Science of The Total Environment, 2024)

Data-driven and knowledge-guided denoising diffusion probabilistic model for runoff uncertainty prediction - Pingping Shao; Jun Feng; Jiamin Lu; Zhixian Tang (Journal of Hydrology, 2024)

Biochar application reduced carbon footprint of maize production in the saline−alkali soils - Sheng Zhang; Lihua Xue; Ji Liu; Longlong Xia; Pingping Jia; Ying Feng; Xingming Hao; Xiaoning Zhao (Agriculture, Ecosystems & Environment, 2024)

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

Sulforaphane inhibits the migration and invasion of BPDE-induced lung adenocarcinoma cells by regulating NLRP12 - Wei Wang; Shufan Chang; Xi He; XiaoLei Zhou; Pingping Shang; Yusong Chen; Xiaoke Wang; Lijuan Chen; Qiao Zhang; Yahong Qiao; Feifei Feng (Toxicology and Applied Pharmacology, 2024)

Development of an electrochemical separation-Rhodopseudomonas palustris electrolysis cell-coupled system for resourceful treatment of mature leachate landfill - Xiaoyan Bai; Yulang Huang; Jian Sun; Chunhua Feng; Yong Yuan; Qintie Lin; Kang Dai; Pingping Zhang (Journal of Environmental Management, 2024)

Mechanistic insights into the adsorption and extraction of rare earth ions using oxygen- and phosphorus-doped porous graphitic carbon nitride - Yiping Feng; Pingping Chen; Xingye Lian; Chenyi He; Chaoyu Zheng; Haijian Lu; Longyong Lin; Guoguang Liu; Yirong Deng (Journal of Environmental Chemical Engineering, 2024)

Interpretable spatial-temporal attention convolutional network for rainfall forecasting - Pingping Shao; Jun Feng; Pengcheng Zhang; Jiamin Lu (Computers & Geosciences, 2024)

Occurrence, distribution, and ecological risk of heavy metals and veterinary antibiotics in soils from citrus orchards: side effects of organic substitution - Pingping Ye; Kunpeng Gao; Hua Feng; Linfa Fang; Dong Li; Jong-Hwan Park; Yueqiang Zhang; Ran Xiao (Journal of Soils and Sediments, 2024)

Potato late blight severity monitoring based on the relief-mRmR algorithm with dual-drone cooperation - Heguang Sun; Xiaoyu Song; Wei Guo; Mei Guo; Yanzhi Mao; Guijun Yang; Haikuan Feng; Jie Zhang; Ziheng Feng; Jiao Wang; Yuanyuan Ma; Chunkai Zheng; et al. (Computers and Electronics in Agriculture, 2023)

Identification of candidate genes related to two economic traits using GWAS in Gracilariopsis lemaneiformis (Rhodophyta) - Xiaoqing Feng; Baoheng Xiao; Min Jiang; Pingping Li; Qiong Wu; Yingtang Dong; Jiaxing Wang; Zhenghong Sui (Algal Research, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Evaluation of time history distribution characteristics of lightning electromagnetic field in heterogeneous soil - Yuanbing Xiang; Pingping Rao; Weikang Feng; Peihao Ouyang (Acta Geophysica, 2023)

A novel design and application of spatial data management platform for natural resources - Weijiang Kong; Tengji Wang; Lili Liu; Pingping Luo; Jianjun Cui; Ligang Wang; Xiankang Hua; Weili Duan; Feng Su (Journal of Cleaner Production, 2023)

The association between urinary polycyclic aromatic hydrocarbon metabolites and liver function among US population: a cross-sectional study - Manthar Ali Mallah; Zhu Ying; Mukhtiar Ali; Junwei Guo; Feifei Feng; Wei Wang; Pingping Shang; Qiao Zhang (Environmental Geochemistry and Health, 2023)

Repeated Digestion by Earthworms on Tetracycline Degrading and Biological Responses in Tetracycline-Contaminated Sewage Sludge - Ping Liu; Taotao Zha; Si-Qi Xia; Pingping Sun; Yu-Feng Wu; Haitao Zhao; Ke Feng (Water, Air, & Soil Pollution, 2023)

Effects of nutrient deficiency on the branch phenotype of the macroalgae Gracilariopsis lemaneiformis (Rhodophyta) - Pingping Li; Haihong Chen; Jingyu Zhang; Xiaoqing Feng; Baoheng Xiao; Yiyi Hu; Zhenghong Sui (Aquaculture, 2023)

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Ploidy Identification by Flow Cytometry and Application of the Method to Characterize Seasonal Ploidy Variation of Wild Populations of the Red Alga Gracilariopsis lemaneiformis - Xiaoqing Feng; Haihong Chen; Baoheng Xiao; Qiong Wu; Jingyu Zhang; Ni Zhang; Pingping Li; Lu Wang; Jingru Yin; Zhenghong Sui (Marine Biotechnology, 2022)

Application of resistivity measurement to stability evaluation for loess slopes - Bin Zhang; Li Feng; Maosheng Zhang; Pingping Sun; Tonglu Li; Hao Liu (Landslides, 2022)

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

rno-miR-128-3p promotes apoptosis in rat granulosa cells (GCs) induced by norepinephrine through Wilms tumor 1 (WT1) - Ming Li; Ling Xue; Weibin Xu; Pingping Liu; Feng Li (In Vitro Cellular & Developmental Biology - Animal, 2021)
The mechanism related to ovarian follicular is complex, which has not been fully elucidated. Abundant reports have confirmed that the ovarian function development is closely related to sympathetic innervation. As one of the major neurotransmitters, norepinephrine (NE) is considered an effective regulator of ovarian functions like granulosa cell (GC) apoptosis. However, the mechanism between NE and GC apoptosis in rat is still unclear. In our study, GCs were isolated and cultured in vitro with NE treatment. The apoptosis of GCs was facilitated by NE. Wilms tumor 1 (WT1) was found to be significantly downregulated in GCs after NE treatment, and overexpression of WT1 repressed apoptosis in rat GCs induced by NE. rno-miR-128-3p was found to be significantly enhanced by NE in GCs, and inhibition of rno-miR-128-3p repressed apoptosis in rat GCs induced by NE. Mechanistically, rno-miR-128-3p interacted with WT1 and repressed its expression. In summary, inhibition of rno-miR-128-3p may enhance WT1 expression, and then repress NE-induced apoptosis in rat GCs. Our research may provide a new insight for the improvement of ovarian follicular development.

Causal associations of waist circumference and waist-to-hip ratio with type II diabetes mellitus: new evidence from Mendelian randomization - Kexin Li; Tianyu Feng; Lijuan Wang; Yang Chen; Pingping Zheng; Pan Pan; Min Wang; Isaac T. S. Binnay; Yingshuang Wang; Ruiyu Chai; Siyu Liu; Bo Li; et al. (Molecular Genetics and Genomics, 2021)

Characterization of Anchorless Human PrP With Q227X Stop Mutation Linked to Gerstmann-Sträussler-Scheinker Syndrome In Vivo and In Vitro - Pingping Shen; Johnny Dang; Zerui Wang; Weiguanliu Zhang; Jue Yuan; Yue Lang; Mingxuan Ding; Marcus Mitchell; Qingzhong Kong; Jiachun Feng; Annemiek J. M. Rozemuller; Li Cui; et al. (Molecular Neurobiology, 2021)
Alteration in cellular prion protein (PrP C ) localization on the cell surface through mediation of the glycosylphosphatidylinositol (GPI) anchor has been reported to dramatically affect the formation and infectivity of its pathological isoform (PrP Sc ). A patient with Gerstmann-Sträussler-Scheinker (GSS) syndrome was previously found to have a nonsense heterozygous PrP-Q227X mutation resulting in an anchorless PrP. However, the allelic origin of this anchorless PrP Sc and cellular trafficking of PrP Q227X remain to be determined. Here, we show that PrP Sc in the brain of this GSS patient is mainly composed of the mutant but not wild-type PrP (PrP Wt ), suggesting pathological PrP Q227X is incapable of recruiting PrP Wt in vivo. This mutant anchorless protein, however, is able to recruit PrP Wt from humanized transgenic mouse brain but not from autopsied human brain homogenates to produce a protease-resistant PrP Sc -like form in vitro by protein misfolding cyclic amplification (PMCA). To further investigate the characteristics of this mutation, constructs expressing human PrP Q227X or PrP Wt were transfected into neuroblastoma cells (M17). Fractionation of the M17 cells demonstrated that most PrP Wt is recovered in the cell lysate fraction, while most of the mutant PrP Q227X is recovered in the medium fraction, consistent with the results obtained by immunofluorescence microscopy. Two-dimensional gel-electrophoresis and Western blotting showed that cellular PrP Q227X spots clustered at molecular weights of 22–25 kDa with an isoelectric point ( p I) of 3.5–5.5, whereas protein spots from the medium are at 18–26 kDa with a p I of 7–10. Our findings suggest that the role of GPI anchor in prion propagation between the anchorless mutant PrP and wild-type PrP relies on the cellular distribution of the protein.

Complementary DNA sequencing (cDNA): an effective approach for assessing the diversity and distribution of marine benthic ciliates along hydrographic gradients - Pingping Huang; Feng Zhao; Kuidong Xu (Journal of Oceanology and Limnology, 2021)

Glutamate and aspartate alleviate testicular/epididymal oxidative stress by supporting antioxidant enzymes and immune defense systems in boars - Wenjie Tang; Jian Wu; Shunshun Jin; Liuqin He; Qinlu Lin; Feijun Luo; Xingguo He; Yanzhong Feng; Binsheng He; Pingping Bing; Tiejun Li; Yulong Yin (Science China Life Sciences, 2020)

Correction to: In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

Decreased decidual epithelial sodium channel (ENaC) alpha and gamma subunits in recurrent pregnancy loss (RPL) - Tiantian Yu; Chun Feng; Pingping Lv; Gufeng Xu; Lihua Hong; Yimeng Xiong; Xiaoyan Guo; Tong Li; Jianzhong Sheng; Hefeng Huang; Xinmei Liu (Science China Life Sciences, 2019)

Evolutionary and functional analyses of the 2-oxoglutarate-dependent dioxygenase genes involved in the flavonoid biosynthesis pathway in tobacco - Zhong Wang; Shanshan Wang; Mingzhu Wu; Zefeng Li; Pingping Liu; Feng Li; Qiansi Chen; Aiguo Yang; Jun Yang (Planta, 2019)

Colon-Targeted Delivery of IgY Against Clostridium difficile Toxin A and B by Encapsulation in Chitosan-Ca Pectinate Microbeads - Pingping Xing; Yanan Shi; Chuangchuang Dong; Hong Liu; Yan Cheng; Junbo Sun; Dalei Li; Min Li; Kaoxiang Sun; Dongxiao Feng (AAPS PharmSciTech, 2017)

Application of SPME-GC/MS to Study the Sorption of Organophosphate Esters on Peat Soil - Chunli Zheng; Shanshan Feng; Qiaorui Wang; Pingping Liu; Zhengxing Shen; Hongxia Liu; Liu Yang (Water, Air, & Soil Pollution, 2016)

Maternal Thyroxine Levels During Pregnancy and Outcomes of Cognitive Development in Children - Pingping Wang; Jian Gao; Shihua Zhao; Yong Guo; Zengfang Wang; Feng Qi (Molecular Neurobiology, 2016)

Transplantation of mesenchymal stem cells improves type 1 diabetes mellitus - Lisha Li; Furong Li; Feng Gao; Yali Yang; Yuanyuan Liu; Pingping Guo; Yulin Li (Cell and Tissue Research, 2016)

Cloning and functional analyses of pepper CaRKNR involved in Meloidogyne incognita resistance - Zhenchuan Mao; Pingping Zhu; Feng Liu; Yonghong Huang; Jian Ling; Guohua Chen; Yuhong Yang; Dongxin Feng; Bingyan Xie (Euphytica, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Soil fertility and its significance to crop productivity and sustainability in typical agroecosystem: a summary of long-term fertilizer experiments in China - Qingyin Shang; Ning Ling; Xumeng Feng; Xiuxia Yang; Pingping Wu; Jianwen Zou; Qirong Shen; Shiwei Guo (Plant and Soil, 2014)

NIPA2 mutations are correlative with childhood absence epilepsy in the Han Chinese population - Yuwu Jiang; Yuehua Zhang; Pingping Zhang; Feng Zhang; Han Xie; Piu Chan; Xiru Wu (Human Genetics, 2014)

NIPA2 located in 15q11.2 is mutated in patients with childhood absence epilepsy - Yuwu Jiang; Yuehua Zhang; Pingping Zhang; Tian Sang; Feng Zhang; Taoyun Ji; Qionghui Huang; Han Xie; Renqian Du; Bin Cai; Haijuan Zhao; Jingmin Wang; et al. (Human Genetics, 2012)

Potential for forest vegetation carbon storage in Fujian Province, China, determined from forest inventories - Yin Ren; Xiaohua Wei; Li Zhang; Shenghui Cui; Feng Chen; Yongzhu Xiong; Pingping Xie (Plant and Soil, 2011)

A note on reviving the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF) dataset - Chung-Lin Shie; Long S. Chiu; Robert Adler; Eric Nelkin; I. -I. Lin; Pingping Xie; Feng-Chin Wang; R. Chokngamwong; William Olson; D. Allen Chu (Advances in Atmospheric Sciences, 2009)

Involvement of JNK regulation in oxidative stress-mediated murine liver injury by microcystin-LR - Yinna Wei; Dan Weng; Feng Li; Xiao Zou; D. Owen Young; Jianguo Ji; Pingping Shen (Apoptosis, 2008)

Lipase-catalyzed selective synthesis of monolauroyl maltose using continuous stirred tank reactor - Qiaoyu Liu; Chengsheng Jia; Jin M. Kim; Pingping Jiang; Xiaoming Zhang; Biao Feng; Shiying Xu (Biotechnology Letters, 2008)

Investigation on arteriosclerosis among population in a rare earth area in South China - Zhü Weifang; Xü Süqin; Wü Dongsen; Shao Pingping; Yang Wenjiao; Zhamg Hui; Feng Jia (Biological Trace Element Research, 1997)

Bioelectrical activity of the central nervous system among populations in a rare earth element area - Weifang Zhu; Suqin Xu; Pingping Shao; Hui Zhang; Dongsen Wu; Wenjiao Yang; Jia Feng (Biological Trace Element Research, 1997)